Weighting with the Lansbury articular index improves the correlation of ultrasound score with serum matrix metalloproteinase-3 level in rheumatoid arthritis patients. Issue 6 (November 2014) - Gorai, Misa; Ogasawara, Michihiro; Matsuki, Yuko; Yamada, Yusuke; Murayama, Go; Sugisaki, Nagachika; Nemoto, Takuya; Ando, Seiichiro; Minowa, Kentaro; Kon, Takayuki; Tada, Kurisu; Matsushita, Masakazu; et al.
Abstract Objective. To determine whether weighting improves the correlation of ultrasound (US) score with serum matrix metalloproteinase-3 (MMP-3) level in rheumatoid arthritis (RA). Methods. As ultrasound examination was performed on 100 RA patients, and the severity of synovial effusion and synovial hypertrophy and the blood flow were semi-quantitatively graded from 0 to 3 by using the gray-scale (GS) and power Doppler (PD) modes. We then calculated the sums of the scores of the 28 joints of each patient in the 2 modes, that is, the GS28 and PD28 scores, as well as the respective scores weighted using the Lansbury articular index (LAI, shoulder and elbow, × 12; wrist, × 8; and knee, × 24)—Lans GS28 and Lans PD28 scores. Result. The Lans PD28 score showed a higher correlation with MMP-3 (r = 0.591; 95% confidence interval, 0.446–0.705, p < 0.0001) than the existing measures. The scores of the large joints—the knee, shoulder, and elbow—correlated well with the serum MMP-3 level. Conclusion. Weighting with the LAI can improve the correlation of US findings with serum MMP-3 level. Bidirectional approach based on both serum MMP-3 level and US scores can further improve the assessment of disease activity in RA patients.